Conceptual Short Term Memory in Perception and Thought - Potter, Mary C. (Frontiers in Psychology, 2012)
Conceptual short term memory (CSTM) is a theoretical construct that provides one answer to the question of how perceptual and conceptual processes are related. CSTM is a mental buffer and processor in which current perceptual stimuli and their associated concepts from long term memory (LTM) are represented briefly, allowing meaningful patterns or structures to be identified (Potter, 1993, 1999, 2009). CSTM is different from and complementary to other proposed forms of working memory: it is engaged extremely rapidly, has a large but ill-defined capacity, is largely unconscious, and is the basis for the unreflective understanding that is characteristic of everyday experience. The key idea behind CSTM is that most cognitive processing occurs without review or rehearsal of material in standard working memory and with little or no conscious reasoning. When one perceives a meaningful stimulus such as a word, picture, or object, it is rapidly identified at a conceptual level and in turn activates associated information from LTM. New links among concurrently active concepts are formed in CSTM, shaped by parsing mechanisms of language or grouping principles in scene perception and by higher-level knowledge and current goals. The resulting structure represents the gist of a picture or the meaning of a sentence, and it is this structure that we are conscious of and that can be maintained in standard working memory and consolidated into LTM. Momentarily activated information that is not incorporated into such structures either never becomes conscious or is rapidly forgotten. This whole cycle – identification of perceptual stimuli, memory recruitment, structuring, consolidation in LTM, and forgetting of non-structured material – may occur in less than 1 s when viewing a pictured scene or reading a sentence. The evidence for such a process is reviewed and its implications for the relation of perception and cognition are discussed.